2021
DOI: 10.3390/foods10092142
|View full text |Cite
|
Sign up to set email alerts
|

Drought and Heat Stress Impacts on Phenolic Acids Accumulation in Durum Wheat Cultivars

Abstract: Droughts and high temperatures are the main abiotic constraints hampering durum wheat production. This study investigated the accumulation of phenolic acids (PAs) in the wholemeal flour of six durum wheat cultivars under drought and heat stress. Phenolic acids were extracted from wholemeals and analysed through HPLC-DAD analysis. Ferulic acid was the most represented PA, varying from 390.1 to 785.6 µg/g dry matter across all cultivars and growth conditions, followed by sinapic acids, p-coumaric, vanillic, syri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
6
27
0
Order By: Relevance
“…As dietary antioxidants, they act as free-radical scavengers [2,3], and reduce the inflammatory response in endothelial cells and monocytes [4]. Besides their antioxidant and antiradical activity, phenolic acids participate in plant cell walls as structural components and are involved in plant adaptation to abiotic and biotic stresses [5,6]. Among other wheat constituents that recently have become a major target of research in wheat there are the Amylase/Trypsin Inhibitors (ATIs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…As dietary antioxidants, they act as free-radical scavengers [2,3], and reduce the inflammatory response in endothelial cells and monocytes [4]. Besides their antioxidant and antiradical activity, phenolic acids participate in plant cell walls as structural components and are involved in plant adaptation to abiotic and biotic stresses [5,6]. Among other wheat constituents that recently have become a major target of research in wheat there are the Amylase/Trypsin Inhibitors (ATIs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids, a major class of polyphenols, are constitutively present in vegetables with strong antioxidant activity [ 36 , 37 ]. Drought stress enhanced the accumulation of phenolic acids [ 29 , 38 ]. In this study, we identified a total of 147 phenolic acids, and nine phenolic acids were considered to be involved in the response to drought stress of Chinese cabbage, including 4−methylphenol, 2−hydroxy−3−phenylpropanoic acid, 3−(4−hydroxyphenyl)−propionic acid, p−coumaric acid methyl ester, methyl sinapate, sinapoyl−4−O−glucoside, curculigine, sinapoylsinapoyltartaric acid, and 1−O−caffeoyl−(6−O−glucosyl)−β−D−glucose.…”
Section: Discussionmentioning
confidence: 99%
“…[12] reported that the accumulation of dry matter decreased due to the reduction in the number of kernels, the green leaf surface during the grain-filling stage decrease when wheat is exposed to high temperatures the number of leaves, the kernel weight and the acceleration of leaf senescence. [13,14]. High temperatures during kernel filling decreased wheat yield by reducing kernel weigh Maximum loss of grain by mechanical damage or incomplete threshing has been reported when grain moisture content had fallen to 15-23 percent Delayed harvest time could increase the grain yield by 59.8 kg ha −1 day −1 and also reported that kernel growth rate increased by 0.3 mg kernel −1 day −1 o C −1 over a temperature range of 25-32 o C [15, 16] Potential nuclear growth did not respond linearly to temperature in the 12-19 o C temperature range [17].…”
Section: Introductionmentioning
confidence: 99%